Distinguishing Molecular Features of Allergic Fungal Rhinosinusitis. (July 2018) - Tyler, Matthew A.; Padro Dietz, Caroline J.; Russell, Chris B.; Citardi, Martin J.; Assassi, Shervin; Ying, Jun; Luong, Amber U.
Objective: Allergic fungal rhinosinusitis (AFRS) is a clinical subtype of chronic rhinosinusitis with nasal polyps (CRSwNP), characterized by eosinophilic mucin, evidence of fungal elements within the mucin, fungal-specific type I hypersensitivity, and characteristic computed tomography findings. It remains controversial whether AFRS represents a disease with a unique pathophysiology from chronic rhinosinusitis or is merely a severe form of CRSwNP. The goal of this study was to identify molecular features unique to AFRS. Study Design: Cross-sectional case-control. Setting: Single academic tertiary referral institution. Subjects and Methods: Subjects included 86 patients undergoing endoscopic sinus surgery: CRSwNP (n = 34), AFRS (n = 37), and healthy controls (n = 15). Pathway and correlation analyses were performed with whole-genome microarray data for study patients undergoing surgery for recalcitrant chronic rhinosinusitis. Our findings were confirmed with quantitative polymerase chain reaction and immunohistochemical studies. Results: AFRS was uniquely characterized by a pronounced association with adaptive T helper 2–associated immune gene expression. AFRS exhibited altered expression of proteins associated with secretory salivary peptides—namely, histatin, a peptide with known antifungal activity in the oral cavity. Furthermore, the expression of histatins correlated negatively with that of type 2 inflammatory mediators. We confirm the decreased expression of histatins in AFRS when compared with CRSwNP by quantitative polymerase chain reaction and localized its expression to a submucosal cell population. Conclusion: There exist clear molecular profiles that distinguish AFRS from CRSwNP. This divergence translates into an altered ability to control fungal growth and may in part explain some of the phenotypical differences between CRSwNP and AFRS.